Hubungan Lama Waktu Kerja dan Masa Kerja dengan Keluhan Musculoskeletal pada Nelayan Tuna di Dusun Rahai Kecamatan Waesala Kabupaten SBB - Maritje S. J Malisngorar; Mega Krisye Beruatwarin; Yerry Soumokil; Rini Hatma Rusli (Lembaga Pengembangan Kinerja Dosen, 2024)
Fishermen are a term for those whose daily work is to catch fish or other biota that live on the seabed or surface waters. The problem that often occurs in musculoskeletal complaints that are often experienced by fishermen is low back pain, this happens because the conditions that fishermen have are not always specific, resulting in pain and soreness in the lower back. Aiming to determine the relationship of Length of Working Time and Working Period with Musculoskeletal Complaints in Fishermen in Rahai Hamlet, Waesala District, West Seram Regency. This study uses quantitative research using a cross sectional design. The sample in the study was 90 people. Data analysis using the Chi-Squere test. The results showed that the p value (0.500) and p value (0.643). This shows that Ha is rejected. It can be concluded that there is no significant relationship between Length of Working Time and Working Period with Musculoskeletal Complaints in Fishermen in Rahai Hamlet, Wesala District, West Seram Regency.